A Tail Does Not Always Make a Difference: Assembly of cds Nets from Co(NCS)2 and 1,4-bis(n-Alkyloxy)-2,5-bis(3,2′:6′,3″-terpyridin-4′-yl)benzene Ligands - Simona S. Capomolla; Giacomo Manfroni; Alessandro Prescimone; Edwin C. Constable; Catherine E. Housecroft (Molecules, 2022)
The consistent assembly of a (65.8) cds net is observed in reactions of cobalt(II) thiocyanate with 1,4-bis(n-alkyloxy)-2,5-bis(3,2′:6′,3″-terpyridin-4′-yl)benzene ligands in which the n-alkyloxy substituents are n-propyl (ligand 3), n-butyl (4), n-pentyl (5), n-hexyl (6), n-heptyl (7), and n-octyl (8). Crystals were grown by layering a methanol solution of Co(NCS)2 over a 1,2-dichlorobenzene solution of each ligand. The choice of crystallization solvents is critical in directing the assembly of the cds net. Single-crystal structures of [Co(NCS)2(3)]n.3.5nC6H4Cl2, [Co(NCS)2(4)]n.5.5nC6H4Cl2, [Co(NCS)2(5)]n.4nC6H4Cl2, [Co(NCS)2(6)]n.3.8nC6H4Cl2, [Co(NCS)2(7)]n.3.1nC6H4Cl2, and [Co(NCS)2(8)]n.1.6nC6H4Cl2.2nMeOH (C6H4Cl2 = 1,2-dichlorobenzene) are presented and compared. The n-alkyloxy chains exhibit close to extended conformations and are accommodated in cavities in the lattice without perturbation of the coordination framework.